STUDI FENOMENOLOGI MOTIF PENGGUNA BRAND LOKAL HIGH END PADA MAHASISWA SURABAYA PENGGUNA BUTTONSCARVES (Universitas Negeri Surabaya, 2023)
This research aims to find out the reasons why Surabaya City Students prefer to use local high end products and this research also aims to find out the motives of Surabaya City Students in using local high end products. The theory in this study uses phenomenological theory based on the views of Alfred Schutz. The approach in this research is qualitative with data collection techniques in the form of observation, interviews and documentation. The results showed that the phenomenon of using the local high end brand Buttonscarves is dominant in the background because Buttonscarves products are able to give the impression of luxury when using Buttonscarves products and provide more value for its users, besides that the quality owned by Buttonscarves cannot be owned by other products. Meanwhile, the internal factors that become the motive for using the local high end brand Buttonscarves are due to the influence of social media, influencers, the needs and encouragement of the closest people, comfort and quality. In addition, external factors in this study are dominated by the level of awareness and brand image of Buttonscarves among the public and the influence of the community. Surabaya students are also active in supporting local brands, students are now very proud when using local brands rather than using foreign brands but not original. Therefore, students support the #Lokalpride movement. Keywords: Phenomenological Study, Motives for Use, Local Brand, High end, Buttonscarves Users